COMPUTATIONAL ANALYSIS OF CHILLI INFECTING PEPPER LEAF CURL LAHOREVIRUS AND PEPPER LEAF CURL BANGLADESH VIRUS - ATIF, M; AHMAD, F; MANZOOR, MT; GILANI, K; ALI, Q; SARWAR, M; ANJUM, S; ALAM, MW; HUSSAIN, A; RAFAQAT, N (Biological and Clinical Sciences Research Journal, 2022)
Since a few decades ago, the pandemic of the Chilli Leaf Curl Disease Complexes (ChiLCD) has caused enormous alarm. The investigations of various genomes isolated from various regions of the subcontinent in the current study revealed a vast expansion of ChiLCD. According to evolutionary research, genomes from the pepper leaf curl Lahore virus (PepLCLV) (JN880419 and JX524173) and the pepper leaf curl Bangladesh virus (PepLCBV) (DQ116881 and KY420149) are ancestors while others are descendants. The accessions JN880419, JX524173, DQ116881, and KY420149’s sequences underwent evolution, giving rise to several strains and variations. According to the findings, the Indian subcontinent’s chilli crop may be most severely affected by the extremely aggressive ChiLCV.